Case report of aplastic anaemia detected in third trimester of pregnancy: dilemmas faced - Kamath, Gayathri Dinesh; Udgire, Sunil Prabhakar; Katewa, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Aplastic anaemia with pregnancy is rarely encountered. Management of aplastic anaemia in pregnancy primarily involves a multidisciplinary approach offering supportive care. Our case was challenging as she developed aplastic anaemia during the third trimester and had refractory thrombocytopenia. She required platelet transfusions on a daily basis for few weeks as well as packed red blood cells frequently. Her leucocyte count was low initially but improved quickly unlike the platelet counts. Initiation of immunosuppressive therapy turned out to be beneficial and culminated in a good outcome. After starting immunosuppressive therapy with eltrombopag and cyclosporine she drifted through term and achieved a normal vaginal delivery.